Textile structures and products
Patent Information
- Application Number
- JP2021028561
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-25
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-02-25
AI Technical Summary
【0016】 本発明によれば、ポリウレタン繊維含有に近い優れたストレッチ性を有しながら、優れた汚れの除去性を有することにより、短時間で汚れを除去することができ、結果として洗濯時に発生する繊維屑量が少ない繊維製品を提供することができる。
Smart Images

Figure 0007639395000005 
Figure 0007639395000006 
Figure 0007639395000007
Abstract
Description
[Technical field]
[0001] The present invention relates to textile structures and textile products. [Background technology]
[0002] In recent years, there has been concern about the adverse effects on ecosystems caused by plastic waste in oceans and rivers being ingested by living organisms. Of particular concern are micro-sized plastic pieces that have been broken down by exposure to ultraviolet light, etc., but there is also discussion about the relevance of all plastic products to waste reduction and the microplastic problem.
[0003] On the other hand, synthetic fibers are widely used in textile products currently on the market, and synthetic fibers may fall off as laundry debris from the cutting section during washing. The resulting laundry debris is collected by a lint collection device of the washing machine.
[0004] Short-staple composite spun yarns, which are made by combining multiple fiber types, such as synthetic and natural staple fibers, and composite spun yarns made of staple and long fibers, are able to incorporate the advantages of various fiber types and are therefore used for a wide range of applications, such as in business shirts and uniforms.
[0005] Also, a method has been proposed in which stains are made easier to remove by performing an antifouling treatment (Patent Documents 1 and 2).
[0006] Meanwhile, in recent years, in order to improve the comfort of wearing for users, composite spun yarns with polyurethane-based elastic long fibers have been used to develop woven fabrics that have the unique texture and performance peculiar to spun yarns while also having stretchability that is difficult to achieve with spun yarns (Patent Document 3). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2019 / 073898 [Patent Document 2] JP 2004-137617 A [Patent Document 3] JP 2020-169401 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, fiber structures using short and short composite spun yarns made by combining multiple fiber types, such as synthetic and natural staple fibers, and composite spun yarns made of short and long fibers, tend to produce a larger amount of fiber waste due to the falling off of short fibers caused by physical impacts such as washing, compared to fiber structures made of only long fibers.
[0009] The stain-resistant finishes described in Patent Documents 1 and 2 alone have excellent stain removability, allowing stains to be removed in a short washing time, and thus reducing the amount of fiber waste generated during washing, but the fabric has poor stretchability (elasticity), making it uncomfortable to wear. In order to improve this, when the technologies described in Patent Documents 1 and 2 are applied to the stretchable woven fabric described in Patent Document 3, since polyurethane elastic fibers are a type of yarn that is more lipophilic than other synthetic fibers, when oily stains adhere to the fibers, they penetrate the fibers, and even if a stain-resistant finish is applied, a long washing time is required to wash off the stains, which tends to result in an increase in the amount of fiber waste.
[0010] Therefore, the present invention relates to a textile product containing synthetic fibers, and an object of the present invention is to provide a textile product which has excellent stretchability close to that of textiles containing polyurethane fibers, while also having excellent stain removability, thereby allowing stains to be removed in a short period of time, and which results in a small amount of fiber waste being generated during washing. [Means for solving the problem]
[0011] In order to solve the above problems, the present invention employs the following configuration.
[0012] (1) A fiber structure at least partially using a composite spun yarn composed of long fibers and short fiber bundles, the latent torque direction of the long fiber and the twist direction of the conjugate spun yarn are opposite to each other, and the long fiber is a bimetal type latent crimping conjugate fiber or an eccentric core-sheath type latent crimping conjugate fiber, A textile structure having soil release properties of grade 3 or higher after a stain resistance evaluation.
[0013] (2) A polyether component is supported on the fiber surface, the weight average molecular weight of the polyether component calculated as polyethylene glycol, obtained by size exclusion chromatography, is in the range of 1500 to 4000 g / mol; The fiber structure according to (1), wherein the ratio of the weight average molecular weight converted into polyethylene glycol to the number average molecular weight converted into polyethylene glycol is within a range of 1.00 to 1.35.
[0014] (3) A fiber structure according to (1) or (2), having a resin coating on at least a part of the fiber surface, the resin coating containing a fluorine-based water- and oil-repellent resin having a polyoxyalkylene group as a hydrophilic component and polyvinyl alcohol.
[0015] (4) A textile product comprising, at least in part, the textile structure according to any one of (1) to (3). Effect of the Invention
[0016] According to the present invention, it is possible to provide a textile product which has excellent stretchability close to that of textiles containing polyurethane fibers, while also having excellent dirt removability, thereby allowing dirt to be removed in a short period of time, and as a result, which generates less fiber waste during washing. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is an example of a bimetal type latent crimpable composite fiber, and is a conceptual diagram of a fiber cross section for illustrating that different polymers are bonded together. [Diagram 2] FIG. 2 is a schematic diagram of a fiber cross section showing an example of an eccentric core-sheath type potentially crimpable conjugate fiber for illustrating the position of the center of gravity in the fiber cross section. [Diagram 3] FIG. 3 is a conceptual diagram of a fiber cross section for explaining the fiber diameter (D) and minimum thickness (S) of an eccentric core-sheath type potentially crimpable conjugate fiber. [Figure 4] FIG. 4 is a conceptual diagram of a fiber cross section for explaining the IFR (the radius of curvature of the interface between components A and B in the fiber cross section) in the fiber cross section of an eccentric core-sheath type potentially crimpable conjugate fiber. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The present invention will be described in detail below. The fiber structure according to the present invention is characterized in that at least a part of the fiber structure contains a composite spun yarn composed of long fibers and short fiber bundles.
[0019] The fiber structure used in the present invention is not particularly limited, and may be a woven fabric or a knitted fabric. When the fiber structure is a woven fabric, the weave structure is not particularly limited, and examples thereof include plain weave, twill weave, satin weave, variable plain weave, variable twill weave, variable satin weave, variegated weave, patterned weave, single-layer weave, double weave, multi-layer weave, warp pile weave, weft pile weave, and leno weave. When the fiber structure is a knitted fabric, the knit structure is not particularly limited, and examples thereof include circular knit, weft knit, warp knit (including tricot knit and raschel knit), pile knit, plain knit, jersey knit, rib knit, smooth knit (double-sided knit), elastic knit, pearl knit, Denbigh weave, cord weave, atlas weave, chain weave, and insertion weave.
[0020] As long as the fiber structure at least partially uses a composite spun yarn composed of long fibers and staple fiber bundles, it may contain synthetic fibers or natural fibers in addition to the composite spun yarn.
[0021] The synthetic fibers are not particularly limited, and examples thereof include polyalkylene terephthalate fibers such as polyethylene terephthalate, polypropylene terephthalate, and polybutylene terephthalate; fibers made of copolymers of dicarboxylic acid components or diol components of polyalkylene terephthalate, such as copolymers of isophthalic acid, isophthalic acid sulfonate, and adipic acid, and copolymers using diol components such as diethylene glycol; aromatic polyester fibers such as modified polyalkylene terephthalate fibers blended with polyethylene glycol; polyester fibers such as aliphatic polyester fibers represented by fibers mainly composed of L-lactic acid; polyamide fibers such as nylon 6 and nylon 66; acrylic fibers mainly composed of polyacrylonitrile; polyolefin fibers such as polyethylene and polypropylene; synthetic fibers such as polyvinyl chloride fibers; and semi-synthetic fibers such as acetate and rayon, among which polyester fibers are preferred. In addition, from the viewpoint of environmental impact, it is preferable to use recycled polyester.
[0022] The recycled polyester referred to here refers to polyester obtained by depolymerizing and repolymerizing polyester recovered after use, which is known as chemical recycled polyester, and polyester obtained by sorting, pulverizing, washing, melting, and repelletizing polyester recovered after use, which is known as material recycled polyester. When using polyester fibers, it is preferable to contain as much recovered polyester resin as possible from the viewpoints of resource reuse and environmental issues. It is preferably 70% by mass or more, and particularly preferably 80% by mass or more. The upper limit may be 100% by mass, but it is preferably 90% by mass or less from the viewpoint of yarn strength.
[0023] The cross-sectional shape of the fiber can be a perfect circle, as well as a variety of other shapes, including flat, triangular, rectangular, hexagonal, octagonal, and other polygonal shapes, as well as a daruma shape with some unevenness, a Y-shape, and a star shape.
[0024] The synthetic fibers may also contain additives such as hindered phenol-based, amine-based, phosphite-based, and thioester-based antioxidants, benzotriazole-based, benzophenone-based, and cyanoacrylate-based ultraviolet absorbers, infrared absorbers, cyanine-based, stilbene-based, phthalocyanine-based, anthraquinone-based, beryllinone-based, and quinacridone-based organic pigments, inorganic pigments, fluorescent whitening agents, particles such as calcium carbonate, silica, and titanium oxide, and electrostatic agents.
[0025] The natural fibers are not particularly limited, and examples thereof include cotton, wool, rayon, cupra fiber, etc. These may be included in any form such as spun yarn, mixed yarn, interwoven, interknitted, mixed cotton, etc.
[0026] In the present invention, from the viewpoints of stretchability, stain resistance, and reduction in fiber waste, a composite spun yarn composed of long fibers and short fiber bundles of bimetal type or eccentric core-sheath type latent crimpable composite fibers is used.
[0027] In order to improve stretchability, polyurethane fibers are generally used, but polyurethane fibers are highly lipophilic and tend to reduce stain resistance, so they are preferably not used in the present invention. If they are used, their amount is preferably 0.1% by mass or less, and more preferably 0.01% by mass or less.
[0028] It is important that the long fibers are bimetallic or eccentric core-sheath type latent crimpable composite fibers.
[0029] The bimetallic latent crimp composite fiber referred to here is a composite fiber having a cross section in which different polymers, A component 1 and B component 2, are bonded together as shown in FIG. 1. As A component 1 and B component 2, polymers with different intrinsic viscosities, copolymerization components, copolymerization rates, etc. are bonded together, and crimping occurs due to the difference in their elastic recovery properties and shrinkage properties. In the case of a bimetallic composite having an intrinsic viscosity difference, stress is concentrated on the high intrinsic viscosity side during spinning and drawing, so the internal strain is different between the two components. Therefore, the high viscosity side shrinks significantly due to the difference in elastic recovery after drawing, and distortion occurs within the single fiber, resulting in a three-dimensional coil crimp. It can be said that the diameter of this three-dimensional coil and the number of coils per unit fiber length are determined by the shrinkage difference (including the difference in elastic recovery) between the high shrinkage component and the low shrinkage component, and the larger the shrinkage difference, the smaller the coil diameter and the greater the number of coils per unit fiber length.
[0030] The coil shrinkage required for a stretch material is a small coil diameter, a large number of coils per unit fiber length (excellent elongation characteristics, good appearance), good coil resistance to settling (small coil settling amount according to the number of stretches, excellent stretch retention), and small hysteresis loss when the coil recovers from elongation (excellent elasticity, good fit), etc. By satisfying all of these requirements while also having polyester properties such as appropriate tension, drapeability, and high color fastness, it is possible to create a stretch material with excellent overall balance.
[0031] Here, the elastic properties of the coil are dominated by those of the high shrinkage component with the low shrinkage component as the fulcrum. Therefore, from the viewpoint of coil properties, it is preferable that the polymer used for the high shrinkage component has high extensibility and recovery properties.
[0032] Suitable polymers for achieving good stretchability include polyethylenes such as polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, and polytrimethylene terephthalate, polyamides, polylactic acid, polyphenylene sulfide, and copolymers thereof. The molecular weights of these polymers may be changed to use a high molecular weight polymer and a low molecular weight polymer, or one component may be a homopolymer and the other component may be a copolymer.
[0033] In addition, examples of combinations of different polymer compositions include various combinations such as polybutylene terephthalate / polyethylene terephthalate, polytrimethylene terephthalate / polyethylene terephthalate, and polytrimethylene terephthalate / polybutylene terephthalate, for component A / component B.
[0034] Among them, by using polyester mainly composed of polybutylene terephthalate (hereinafter abbreviated as PBT) as a high shrinkage component, excellent elastic recovery and elongation recovery can be obtained while having mechanical and chemical properties equivalent to those of polyethylene terephthalate (hereinafter abbreviated as PET) and polytrimethylene terephthalate (hereinafter abbreviated as PTT) fibers, which are typical polyester fibers. This is thought to be because the methylene chain of the alkylene glycol part in the crystal structure of PBT has a gauche-gauche structure (molecular chain is bent at 90 degrees), and further, the density of constraint points due to the interaction between benzene rings (stacking, parallel) is low, resulting in high flexibility, and the molecular chain easily elongates and recovers due to the rotation of the methylene group.
[0035] Here, the PBT in the present invention is a polyester obtained by polycondensation of terephthalic acid or its derivative as the main acid component and 1,4-butanediol or its derivative as the main glycol component. However, it may contain a copolymerization component capable of forming other ester bonds at a ratio of 20 mol %, more preferably 10 mol % or less of the total acid components or total glycol components. Examples of copolymerizable compounds include dicarboxylic acids such as isophthalic acid, succinic acid, cyclohexanedicarboxylic acid, adipic acid, dimer acid, sebacic acid, and 5-sodium sulfoisophthalic acid, and diols such as ethylene glycol, diethylene glycol, butanediol, neopentyl glycol, cyclohexanedimethanol, polyethylene glycol, and polypropylene glycol, but are not limited thereto.
[0036] Furthermore, the low-shrinkage component (low-viscosity component) is not particularly limited as long as it is a fiber-forming polyester that has good interfacial adhesion with the high-shrinkage component PBT and stable spinnability, but considering the mechanical properties, chemical properties, and raw material costs, PET, which has fiber-forming ability, is preferred.
[0037] From the viewpoints of spinnability and dimensional uniformity of the coil in the fiber length direction, the compounding ratio of the two components is preferably high shrinkage component:low shrinkage component (mass ratio)=75:25 to 35:65, more preferably 65:35 to 45:55.
[0038] As shown in Fig. 2, an eccentric core-sheath type latent crimpable conjugate fiber is a conjugate fiber having a cross section in which a core component A 3 is surrounded by a sheath component B 4, and has a composite cross section in which two types of polymers having different shrinkage characteristics due to differences in intrinsic viscosity, polymer type, copolymerization component, copolymerization rate, etc. are bonded together as the A component 3 and the B component 4, as in the above-mentioned bimetal type latent crimpable conjugate fiber. Of these, it is preferable that the two types of polymers with different polymer properties exist in a bonded state without being substantially separated, and that the A component completely covers the B component.
[0039] In FIG. 2, the shaded portion is component B 4, the white portion is component A 3, the center of gravity of component A in the cross section of the composite fiber is center of gravity a5, and the center of gravity of the cross section of the composite fiber is center of gravity C6.
[0040] In the above-mentioned eccentric core-sheath type potentially crimpable composite fiber, it is preferable that the center of gravity a5 of the A component 3 is far from the center of gravity C6 of the composite fiber cross section, so that the fiber will be significantly curved toward the high shrinkage component after heat treatment. As a result, the composite fiber continues to bend in the fiber axis direction, forming a three-dimensional spiral structure and exhibiting good crimp. Here, the farther the center of gravity is, the better the crimp will be, and the better the stretch performance will be.
[0041] In the eccentric core-sheath type latent crimpable composite fiber used in the present invention, the ratio S / D of the minimum thickness S7 of the B component 4 covering the A component 3 to the fiber diameter (diameter of the composite fiber) D8 is preferably 0.01 to 0.1, and more preferably 0.02 to 0.08. Within this range, excellent abrasion resistance and sufficient crimp development and stretch performance can be obtained.
[0042] This will be explained in more detail using the fiber cross section shown in FIG.
[0043] Here, in a cross section of an eccentric core-sheath type potentially crimpable conjugate fiber cut in a direction perpendicular to the fiber axis, the length of the part where component B is thinnest is the minimum thickness S7.
[0044] Furthermore, it is preferable that the perimeter of the portion with a thickness within 1.05 times the minimum thickness S is 1 / 3 or more of the entire perimeter of the composite fiber. This means that component A is present along the contour of the fiber, and compared with conventional eccentric core-sheath composite fibers with the same area ratio, the present invention has the centers of gravity of the respective components farther apart in the fiber cross section, forming a fine spiral and exhibiting good crimp. More preferably, by making the perimeter of the portion with a thickness within 1.05 times the minimum thickness S 2 / 5 or more of the entire perimeter of the fiber, good stretch performance can be obtained without crimp unevenness.
[0045] Furthermore, it is preferable that the radius of curvature IFR9 of the interface between components A and B in the fiber cross section satisfies the following formula 1 when the value R is obtained by dividing the fiber diameter D8 by 2. The radius of curvature IFR9 here refers to the radius of a circle (dashed line) tangent to the curvature of the interface between components A and B, which is the maximum thickness of component B covering component A in the fiber cross section as shown in Fig. 4. (IFR / R)≧1···(Formula 1)
[0046] This means that the interface is closer to a straight line. The present invention is preferable because it is possible to realize high crimp that could not be achieved with conventional eccentric core-sheath composite fibers by making the interface between components A and B a curve close to a straight line in a form similar to the cross section of conventional laminated crimped fibers. More preferably, it is 1.2 or more.
[0047] The minimum thickness S of component B covering component A, the fiber diameter D, the interface curvature radius IFR, and the area ratio of components A and B are calculated as follows:
[0048] That is, the eccentric sheath-core composite fiber is embedded in an embedding agent such as epoxy resin, and an image of the cross section is taken with a transmission electron microscope (TEM) at a magnification where 10 or more fibers can be observed. In this case, if metal staining is applied, the contrast of the joint between the A component and the B component can be made clear by utilizing the dyeing difference between the polymers. The value obtained by measuring the circumscribed circle diameter of 10 fibers randomly extracted from each of the images taken corresponds to the fiber diameter D referred to in the present invention. Here, if it is impossible to observe 10 or more fibers, other eccentric sheath-core composite fibers may be observed, and a total of 10 or more fibers may be observed, including these. The circumscribed circle diameter referred to here means the diameter of a perfect circle that circumscribes the most at two or more points on a cross section perpendicular to the fiber axis in a two-dimensionally photographed image.
[0049] In addition, the image in which the fiber diameter D was measured is used to measure the minimum thickness of component B covering component A for 10 or more fibers, and the value corresponds to the minimum thickness S referred to in the present invention. Furthermore, the fiber diameter D, minimum thickness S, and radius of curvature IFR are measured in units of μm, and are rounded off to the nearest third decimal place. The simple number average of the measured values and their ratios (S / D) is calculated for 10 images photographed after the above operations.
[0050] In addition, the area ratio of components A and B was calculated by using the image captured as described above and the image analysis software "WinROOF2015" manufactured by Mitani Shoji Co., Ltd. to calculate the area of the entire fiber and the areas of components A and B, and then calculating the area ratio.
[0051] As the single fibers constituting the short fiber bundles used in the composite spun yarn, the above-mentioned synthetic fibers and natural fibers can be used.
[0052] Of these, from the viewpoint of environmental impact, it is preferable to use polyester (more preferably recycled polyester) as the synthetic fiber, and cotton, wool, rayon, and cupra as the natural fiber.
[0053] The above-mentioned short fibers are not particularly limited, but can be made into a fleece-like short fiber bundle using a common spinning machine such as a ring spinning machine, an air spinning machine, or an MVS machine.
[0054] The composite spun yarn used in the present invention is composed of long fibers and short fiber bundles, and is preferably a long-short composite yarn using long fibers as the core yarn and short fiber bundles as the sheath yarn.
[0055] As a spinning method for the long and short composite yarn, ring spinning, air spinning, etc. can be preferably used, but from the viewpoint of stretch back property and quality, ring spinning is more preferably used.
[0056] The count of the long and short composite yarn used in the present invention is not particularly limited, but in producing the long and short composite spun yarn, it is preferable to determine the count so that the number of staple fibers constituting the cross section of the long and short composite spun yarn is 50 or more. The twist number T should be set slightly lower than that of general long and short composite spun yarn, and preferably in the range of K=3.0 to 4.0 where T (turns / 2.54 cm)=K (cotton count)1 / 2 (K: twist coefficient).
[0057] In the present invention, the mass ratio of long fibers / short fibers is preferably 15 to 85 / 85 to 15. When the mass ratio is within this range, the combined effect of using both long and short fibers is significantly exhibited.
[0058] The potential torque direction here refers to the potential torque of the continuous fibers (fiber bundles made of bimetallic or eccentric core-sheath type composite fibers), and is different from the torque caused by twisting during spinning.
[0059] The fiber structure of the present invention can exhibit good stretchability by twisting the short fiber bundles with the long fibers and spinning the short fiber bundles in a direction opposite to the latent torque direction of the long fibers. For example, if the latent torque direction of the long fibers is the Z direction, twisting the short fiber bundles in the S direction and spinning them generates a torque in the opposite direction to the twist direction, which creates a strong crimp in a synergistic effect with the latent torque direction of the long fibers, resulting in stronger stretchability.
[0060] The single fiber fineness of the bimetallic or eccentric core-sheath type potentially crimpable composite fiber used in the present invention is preferably 1.1 to 10 dtex, more preferably 1.1 to 6 dtex. By making the single fiber fineness 1.1 dtex or more and 3.0 dtex or less, it is possible to obtain the effect of stretchability due to crimp and suppression of wrinkles.
[0061] The fineness of the staple fibers is not particularly limited, but is preferably within the range of 0.6 to 5 dtex in consideration of spinning properties. The fiber length of the staple fibers should be set according to the various spinning methods, but for example, when air spinning or ring spinning is used, a fiber length of 25 mm to 51 mm is preferably used in consideration of the spinning principle, and a fiber length of 30 mm to 44 mm is more preferable.
[0062] Furthermore, the bimetal or eccentric sheath-core latent crimpable composite fibers constituting the composite spun yarn used in the present invention preferably have an elongation recovery rate of 80% or more when elongated by 20%. If this elongation recovery rate is 80% or more, when the fibers are spun into a composite yarn using, for example, a ring spinning machine, they can be tightly entangled with the short fiber component due to their excellent stretch-back properties and crimp expression, and can provide a so-called long-short composite spun yarn that has excellent shape stability of the sheath-core structure, a fluffy feel, and high stretchability, and can provide good stretchability when woven into a fabric.
[0063] The total fineness of the bimetal or eccentric core-sheath type latent crimpable composite fiber used in the present invention is preferably 20 dtex to 100 dtex. If the total fineness is less than 20 dtex, the characteristics of the short fiber bundle become the characteristic of the composite spun yarn, making it difficult to achieve the effects of the present invention. If the total fineness exceeds 100 dtex, the number of fibers constituting the short fiber bundle decreases, and the core yarn is exposed in the sheath part of the composite spun yarn. The total fineness of the long fiber used in the composite spun yarn, which is particularly suitable for use in shirting fabrics, is preferably 25 dtex to 60 dtex.
[0064] Furthermore, the number of filaments in the bimetal type or eccentric core-sheath type latent crimpable conjugate fiber used in the present invention is determined by the total fineness and the staple fiber fineness. From the viewpoints of softness to bending and texture when made into a woven fabric, the number of filaments is preferably 6 to 46, and from the viewpoints of stretchability and suppression of crimping during processing, the number of filaments is more preferably 12 to 36.
[0065] In the present invention, the above-mentioned fiber structure is usually subjected to a functional treatment such as a stain-resistant treatment so as to satisfy the soil release property (SR property) defined in the present invention. The stain-resistant treatment is preferable because it enables stains to be removed in a shorter washing time, which leads to a reduction in the amount of fiber waste.
[0066] The method of stain-resistant processing is not particularly limited, but it may be to improve soil release properties (ability to remove stains during washing) (SR properties), or to improve stain adhesion prevention properties (SG properties), or both may be combined.
[0067] As a method for improving the SR property, a hydrophilic component that contributes to improving the SR property may be supported on the fiber surface.
[0068] One method for improving the SG property is to apply an agent with excellent water and oil repellency, such as a fluorine-based water repellent, to the fiber surface (water repellent treatment).
[0069] In order to improve both the SR and SG properties, a method of applying an agent having weak water- and oil-repellency, such as a fluorine-based water-repellent agent having a hydrophilic component such as a polyoxyalkylene group (weak water- and oil-repellent treatment) can be mentioned.
[0070] On the other hand, the use of a water repellent alone that does not have oil repellency, such as a non-fluorinated water repellent, is inappropriate because it leads to a decrease in the ability to remove dirt.
[0071] In the present invention, in addition to the above-mentioned stain-resistant finish, antistatic, flame-retardant, moisture-absorbing, antistatic, antibacterial, softening and other known functional finishes may be used in combination.
[0072] As a method for supporting a hydrophilic component that contributes to improving the SR property (stain removability during washing) on the fiber surface as exemplified above, there is specifically a method of providing a hydrophilic component such as polyether, polycarboxylic acid, polysulfonic acid and its salt, cationic surfactant, etc. Among them, from the viewpoint of stain resistance and reduction of fiber waste, it is preferable to support a polyether component with a small molecular weight distribution (variation in molecular weight) on the fiber surface of a polyester fiber structure.
[0073] The molecular weight distribution is a value indicating the variation in molecular weight, and is calculated from the ratio of the weight average molecular weight converted into polyethylene glycol to the number average molecular weight converted into polyethylene glycol (weight average molecular weight / number average molecular weight). By narrowing the molecular weight distribution, that is, by reducing the variation in molecular weight, the antifouling properties specified in the present invention are satisfied. In particular, it is preferable to use a polyether having a relatively uniform molecular weight, such as 1.00 to 1.35, and more preferably 1.00 to 1.25, from the viewpoint of imparting a more excellent antifouling property. It is more preferably 1.00 to 1.20.
[0074] Furthermore, the weight average molecular weight of the polyether component used, calculated as polyethylene glycol and obtained by size exclusion chromatography, is preferably large enough to satisfy the antifouling property defined in the present invention, and in particular, it is preferable to use a relatively high molecular weight polyether such as 1500 to 4000 g / mol from the viewpoint of imparting a more excellent antifouling property, and more preferably 2000 to 4000 g / mol.
[0075] Methods for supporting a polyether component on the fiber surface include post-processing with a processing agent containing a polyether component by bath treatment, pad method, etc., as well as methods of copolymerizing or graft polymerizing a polyether or a copolymerizable monomer having a polyether group with a base polymer constituting the fiber that constitutes the polyester fiber structure, and raw yarn modification such as kneading into the fiber. However, in the case of raw yarn modification, there is a possibility that physical properties such as yarn strength may change significantly or that dirt may easily penetrate into the fiber. Therefore, post-processing treatments such as bath treatment and pad method, which can selectively modify the surface without impairing physical properties, are preferred.
[0076] In the present invention, the polyether component means a polyether or a polyether group portion in a compound containing a polyether group. The polyether component refers to a compound having two or more ether bonds per molecule, or a polyether group present in the molecule. Examples of compounds that can be used to support the polyether component on the fiber structure of the present invention include polyalkylene glycol, cellulose, and block copolymers consisting of polyalkylene glycol and polyester, but are not limited thereto as long as the provisions of the present invention are satisfied. Among them, a polyetherester block copolymer in which a segment A consisting of a polyalkylene glycol unit and a segment B consisting of a polymer unit copolymerizable with the polyalkylene glycol, such as polyester, are copolymerized is preferred from the viewpoint of high affinity with polyester-based fibers and durability such as washing resistance.
[0077] Preferred examples of the polyalkylene glycol unit constituting the above segment A include units formed from polyethylene glycol, polypropylene glycol, and polybutylene glycol, and among these, units formed from polyethylene glycol are more preferred.
[0078] As a preferred example of the polyester unit constituting the above-mentioned segment B, a polymer unit composed of terephthalic acid / or isophthalic acid and alkylene glycol is preferably exemplified.
[0079] The copolymerization ratio of polyester and polyether in these block copolymers is arbitrary, but from the viewpoint of imparting better stain resistance, the polyester unit:polyether unit (mass ratio) is preferably 1:1 to 1:30. More preferably, the polyester unit:polyether unit (mass ratio) is 1:1 to 1:10. Still more preferably, the polyester unit:polyether unit (mass ratio) is 1:1 to 1:3.
[0080] In addition, with regard to the processing for supporting a hydrophilic component that contributes to improving the SR properties on the fiber surface, it is preferable that the processed fiber structure exhibits a water repellency of Grade 1, an oil repellency of Grade 0 or higher, and a water absorption time of 3 seconds or less as measured by the JIS L 1907-Dropping Method (2010). In particular, a water absorption time of 1 second or less is more preferable in terms of improving the dirt removal properties.
[0081] As described above, it is preferable to use an agent having excellent water and oil repellency as the water repellent treatment for improving the dirt adhesion prevention property (SG property). Examples of the water repellent used in the water repellent treatment include fluorine-based water repellents having a perfluoroalkyl group with 7 or more carbon atoms, and fluorine-based water repellents having a perfluoroalkyl group with 6 or less carbon atoms (for example, Daikin Industries, Ltd.'s "Unidyne" TG-5546, "Unidyne" TG-5601, Asahi Glass Co., Ltd.'s "Asahi Guard" AG-E061, "Asahi Guard" AG-E081), and it is preferable to apply these to the fiber surface. These can be used alone or in combination of two or more. Among them, fluorine-based water repellents having a perfluoroalkyl group with 6 or less carbon atoms are preferable. In recent years, there has been a tendency to avoid the use of perfluorooctanoic acid and perfluorooctanesulfonic acid, so it is preferable that the content of perfluorooctanoic acid and perfluorooctanesulfonic acid in the fiber structure is less than 5 ppm.
[0082] The use of a crosslinking agent together with the water repellent agent can impart washing durability. Preferred examples of such crosslinking agents include "Amidea" M-3 (trimethylol melamine) and MBX-31 (blocked isocyanate) manufactured by DIC Corporation.
[0083] Furthermore, a catalyst can be used to accelerate the reaction of the crosslinking agent. A preferred example of such a catalyst is "Catalyst" ACX (amine catalyst) manufactured by DIC Corporation.
[0084] Methods for imparting a water repellent to a fiber structure include post-processing methods such as bath treatment and the Pad method, as well as yarn modification such as kneading into the fiber. However, in the case of yarn modification, physical properties such as yarn strength may change significantly, so post-processing such as the Pad method, which does not impair physical properties, is preferred.
[0085] The textile structure after the water-repellent treatment for improving the dirt adhesion prevention property (SG property) is preferably highly water- and oil-repellent. Moreover, the textile structure being highly water- and oil-repellent means that the textile structure has a water repellency of grade 4 or less, an oil repellency of grade 5 or more, and a water absorption measured by JIS L 1907-Dropping method (2010) of 60 seconds or more.
[0086] As a method for improving both the SG property and the SR property, as described above, a method of applying an agent having weak water- and oil-repellent properties, such as a fluorine-based water- and oil-repellent agent having a hydrophilic component such as a polyoxyalkylene group (weak water- and oil-repellent processing) or a method of applying an agent having water- and oil-repellent properties (water- and oil-repellent processing) is preferred, and among these, it is preferred to form a coating containing a fluorine-based water- and oil-repellent component having a polyoxyalkylene group and polyvinyl alcohol on at least a part of the fiber surface.
[0087] As the fluorine-based water- and oil-repellent component having a polyoxyalkylene group, it is preferable that it has weak water-repellency and oil-repellency as described above, and specifically, it is preferable that it is a fluorine-containing copolymer having a repeating unit derived from a vinyl monomer having a perfluoroalkyl group and a vinyl monomer having a hydrophilic functional group (hydrophilic vinyl monomer).
[0088] As the vinyl monomer having a perfluoroalkyl group, a vinyl monomer having a perfluoro group having 6 or less carbon atoms is preferably used, and more preferably one containing a repeating unit derived from CH2=C(CH3)C(=O)OCH2CH2(CF2)5CF3 is used.
[0089] The fluorine-based weakly water- and oil-repellent resin preferably has a perfluorooctanoic acid and perfluorooctanesulfonic acid content below the detection limit, which means that the concentrations of perfluorooctanoic acid, perfluorooctanesulfonic acid, their precursors, and their salts measured by a high performance liquid chromatograph-mass spectrometer (LC-MS) shown below are all less than 5 ng / g. Equipment: LC-MS / MS tandem mass spectrometer TSQ-7000 (Thermo Electron) High-performance liquid chromatograph LC-10Avp (Shimadzu Corporation) Column: Capcellpak C8 100mm x 2mm i.d. (5μm) Mobile phase: A; 0.5mmol / L ammonium acetate B; acetonitrile Flow rate: 0.2mL / min Sample injection volume: 3μL CP temperature: 220℃ Ionization voltage: 4.5kv Ion Multi: 1300v Ionization method: ESI-Negative
[0090] The average degree of polymerization of polyvinyl alcohol is usually from 100 to 3,500, and preferably from 200 to 1,500.
[0091] Examples of the hydrophilic vinyl monomer include vinyl monomers containing a hydrophilic functional group such as a sulfonyl group, a sulfonyl base, a carboxyl group, a carboxyl base, an ammonium group, an oxyalkylene group, or a polyoxyalkylene group. Among these, vinyl monomers represented by the following general formula (II) are preferred. CH2=CR1C(=O)O-(R2O)n-R3(II)
[0092] In the formula, R1 is usually H or an alkyl group having 1 to 4 carbon atoms, and preferably H or CH3. -(R2O)n- represents an oxyalkylene group or a polyoxyalkylene group. R2 is usually preferably an alkylene group having 2 to 5 carbon atoms, and is more preferably CH2CH2, CH2CH2CH2 or CH2(CH3)CH2 in that the hydrophilicity can be controlled to a more preferred range. R3 usually represents H or CH3. n represents the degree of polymerization, and is 1 to 20.
[0093] The ratio of the vinyl monomer having a perfluoroalkyl group to the hydrophilic vinyl monomer in the fluorine-containing copolymer preferably used above is not limited as long as it satisfies the range specified in the present invention, but it is preferable to control it by the following method so as to have weak water- and oil-repellency and water- and oil-absorption repellency. The control can be performed by the following method. That is, by increasing the ratio of the vinyl monomer having a hydrophilic functional group, the water repellency can be suppressed, and to increase the oil repellency, the ratio of the vinyl monomer having a perfluoroalkyl group can be increased.
[0094] Also, even if the ratio is the same, the hydrophilicity of the vinyl monomer containing the hydrophilic functional group can be increased. As a method for this, the ratio of the hydrophilic functional group can be increased, or a functional group with higher hydrophilicity can be selected as the hydrophilic functional group to reduce the water repellency. The hydrophilic functional group is preferably an oxyalkylene group (more preferably an oxyethylene group) or a polyoxyalkylene group (more preferably a polyoxyethylene group). When a polyoxyalkylene group is used, the hydrophilicity can be increased by increasing the degree of polymerization.
[0095] It is also possible to improve oil repellency by increasing the number of carbon atoms in the perfluoroalkyl group in the vinyl monomer having the perfluoroalkyl group.
[0096] The textile structure after the weak water- and oil-repellent treatment is preferably weakly water- and oil-repellent. In addition, the textile structure being weakly water- and oil-repellent means that the textile structure has a water repellency of grade 2 or less, an oil repellency of grade 2 or more, and a water absorbency of 40 seconds or more as measured by JIS L 1907-Dropping Method (2010).
[0097] The textile structure after the water-absorbing and oil-repellent treatment is preferably water-absorbing and oil-repellent. Moreover, the textile structure being water-absorbing and oil-repellent means that the water repellency of the textile structure is class 2 or less, the oil repellency is class 2 or more, and the water absorption measured by JIS L 1907-Dropping Method (2010) is less than 40 seconds. Here, the water repellency of the textile structure having water-absorbing and oil-repellent properties is preferably class 1 or less.
[0098] The fiber structure is more preferably weakly water- and oil-repellent. In addition, when the fiber structure is weakly water- and oil-repellent, the water absorbency of the fiber structure measured by JIS L 1907-Dropping method (2010) is more preferably 60 seconds or more, because this improves the washing durability of the stain removability of the fiber structure. In addition, when the fiber structure is weakly water- and oil-repellent, the oil repellency of the fiber structure is more preferably grade 7 or less, in terms of the balance between stain resistance and affinity with wash water.
[0099] The average degree of polymerization of polyvinyl alcohol is usually from 100 to 3,500, and preferably from 200 to 1,500.
[0100] Polyvinyl alcohol may be produced by saponifying polyvinyl acetate. The degree of saponification of polyvinyl alcohol is preferably from 70 to 99%, more preferably from 80 to 95%.
[0101] The average polymerization degree and the degree of saponification are values obtained by measurements in accordance with JIS K 6726 (1994), Sections 3.7 and 3.5, respectively.
[0102] The ratio of the fluorine-based water- and oil-repellent component to polyvinyl alcohol used in the present invention is usually 5 to 60 parts by weight, preferably 10 to 40 parts by weight, of polyvinyl alcohol per 100 parts by weight of the solid content of the fluorine-based water- and oil-repellent component.
[0103] The polyvinyl alcohol used in the present invention may contain a functional group other than a hydroxyl group or an acetate group, such as an acetoacetyl group, a sulfonyl group, a sulfonyl base, a carboxyl group, a carboxyl base, a quaternary ammonium base, an oxyalkylene group, a polyoxyalkylene group, an alkyl group, an alkenyl group, an alkynyl group, or a phenyl group. The amount of the fluororesin and polyvinyl alcohol adhering to the fiber as solids is 0.2 to 1.0% by mass, preferably 0.4 to 0.8% by mass, in which case the stain removal performance can be sufficiently exhibited and the texture is soft, which is preferable.
[0104] In addition, similar to the water repellent, washing durability can be imparted by using a crosslinking agent in combination. Preferred examples of such crosslinking agents include "Amidea" M-3 (trimethylol melamine) and MBX-31 (blocked isocyanate) manufactured by DIC Corporation.
[0105] Furthermore, a catalyst can be used to accelerate the reaction of the crosslinking agent. A preferred example of such a catalyst is "Catalyst" ACX (amine catalyst) manufactured by DIC Corporation.
[0106] In addition, in the present invention, antibacterial processing may be used in combination. This is preferable because it can suppress the formation of dirt that is firmly accumulated on the fiber, called a biofilm, by using contaminants such as sebum attached to the fiber structure as a nutrient source. The type of antibacterial agent is not limited, but examples include pyridine-based antibacterial agents and silver-based antibacterial agents, and among them, pyridine-based antibacterial agents are preferred.
[0107] The pyridine-based antibacterial agent is not particularly limited, and examples thereof include pyridine-based antibacterial agents such as 2-chloro-6-trichloromethylpyridine, 2-chloro-4-trichloromethyl-6-methoxypyridine, 2-chloro-4-trichloromethyl-6-(2-furylmethoxy)pyridine, di(4-chlorophenyl)pyridylmethanol, 2,3,5-trichloro-4-(n-propylsulfonyl)pyridine, 2-pyridylthiol-1-oxide zinc, and di(2-pyridylthiol-1-oxide). Compounds, N-trichloromethylthiophthalimide, N-1,1,2,2-tetrachloroethylthiotetrahydrophthalimide, N-trichloromethylthiotetrahydrophthalimide, N-trichloromethylthio-N-(phenyl)methylsulfamide, N-trichloromethylthio-N-(4-chlorophenyl)methylsulfamide, N-(1-fluoro-1,1,2,2-tetrachloroethylthio)-N-(phenyl)methylsulfamide, N-(1,1-difluoro-1,2,2-tetrachloroethylthio)-N-(phenyl)methylsulfamide, haloalkylthio compounds such as N,N-dichloroethylthio-N-(phenyl)methylsulfamide, N,N-dichlorofluoromethylthio-N'-phenylsulfamide, N,N-dimethyl-N'-(p-tolyl)-N'-(fluorodichloromethylthio)sulfamide, 1-diiodomethylsulfonyl-4-chlorobenzene, 3-iodo-2-propargylbutylcarbamic acid, 4-chlorophenyl-3-iodopropargylformal, 3-ethoxycarbonyloxy-1-bromo- Examples of compounds that can be used include organic iodine compounds such as 1,2-diiodo-1-propene and 2,3,3-triiodoallyl alcohol, thiazole compounds such as 4,5-dichloro-2-cyclohexyl-4-isothiazolin-3-one, 2-(4-thiocyanomethylthio)benzthiazole and 2-mercaptobenzthiazole zinc, and benzimidazole compounds such as 1H-2-thiocyanomethylthiobenzimidazole and 2-(2-chlorophenyl)-1H-benzimidazole.
[0108] Methods for incorporating an antibacterial agent include post-processing methods such as bath treatment and the Pad method, as well as raw yarn modification such as kneading into the fibers. However, in the case of raw yarn modification, physical properties such as yarn strength may change significantly, so post-processing methods such as bath treatment and the Pad method that do not impair physical properties are preferred.
[0109] When the fiber structure is made into a fiber product, cutting or the like can be performed as necessary. The cutting method is not particularly limited, but ultrasonic welding is preferably selected. In this cutting method, the cut part is welded, which can suppress fraying of the fibers and the generation of fiber waste falling off from the cut part.
[0110] The thus obtained fiber structure can be used for various purposes such as business shirts, uniforms, sportswear, casual wear, and bedding. EXAMPLES
[0111] (Method for measuring weight-average molecular weight in terms of polyethylene glycol) The weight average molecular weight calculated as polyethylene glycol was measured under the following conditions. Apparatus: Gel permeation chromatograph GPC (Shimadzu Corporation LC-20AD) Detector: Differential refractive index detector RI (Waters RI-8020 type, sensitivity 32x) Column: TSKgel G3000PW XL (Manufactured by Tosoh) Solvent: 0.1M sodium chloride solution Flow rate: 0.8 mL / min Column temperature: 23℃ Injection volume: 0.1 mL Standard samples: polyethylene glycol, polyethylene oxide Data processing: Shimadzu Prominence GPC system
[0112] The sample preparation method is shown below. 1. Add 5 g of polyester fiber structure and 30 mL of ammonia water to a test tube and seal. 2.Heat at 120℃ for 5 hours and allow to cool. 3. Open the cap and add 30 mL of purified water, then add 6 M hydrochloric acid until a precipitate derived from terephthalic acid appears, and centrifuge. 4. Collect the supernatant and adjust the hydrochloric acid concentration to 0.1M. 5. The mixture was filtered through a 0.45 μm filter and used for molecular weight measurement.
[0113] When polyethylene terephthalate fibers are used and the polyether component is a polyethylene glycol component, the above measurement may detect ethylene glycol components derived from polyethylene terephthalate. In this case, taking into account the purpose of the measurement, the polyethylene glycol component is the subject of evaluation.
[0114] (NMR measurement) The same procedure as in sample preparation methods 1 to 3 for measuring the weight average molecular weight in terms of polyethylene glycol was carried out, and 5 mL of the resulting supernatant was dried and then dissolved in 1 mL of 50% deuterated chloroform / deuterated hexafluoro-2-propanol. The solution was placed in an NMR tube and measured using the following measurement method. 1 H-NMR measurements were performed.
[0115] When the peak derived from the internal standard tetramethylsilane is set at 0 ppm in the NMR spectrum chart, a strong peak is detected at 3.7 to 3.8 ppm, indicating the presence of a polyethylene glycol component.
[0116] ( 1 H-NMR measurement method) [conditions] Device name: ECA400 (manufactured by JEOL) Measuring nucleus: 1H Observation frequency: 399.78 MHz Solvent: Deuterated chloroform + deuterated hexafluoro-2-propanol (1 / 1 v / v) Internal standard: Tetramethylsilane (TMS) [detail] Measurement method: Single pulse Spectral width: 8000 Hz Pulse width: 6.45 μs (45° pulse) Pulse waiting time: 15.0 s Data points: 32768
[0117] (Method for measuring polyester / polyether copolymer ratio) 1. Add 5 g of polyester fiber structure and 30 mL of HFIP / chloroform mixed solvent to a test tube and seal it. 2. Stir to dissolve the polyester fiber structure in the solvent. 3. Filter the solution and evaporate only the soluble portion. 4. 30 mL of water is added to the dried product, and after stirring, the precipitate derived from the polyester fibers is centrifuged so that only the polymer formed by polymerization of the polyether component dissolved in water is dissolved in the supernatant. 5. Collect the supernatant and calculate the copolymerization ratio based on the peak intensity ratio of the NMR measurement above.
[0118] (Water repellency) The water repellency was evaluated using the spray method according to the method specified in JIS L 1092 "Testing method for waterproofing of textile products" (2009), and a grade was given to the water repellency. The grade was determined by n=3 evaluations. Water repellency is graded from grade 1 to grade 5, with the higher the number, the higher the water repellency. The grade was determined by the attached photo attached to JIS L 1092.
[0119] (Oil repellency) Oil repellency was measured according to the method specified in AATCC 118 and graded. Oil repellency is graded from grade 1 to grade 8, with the higher the number, the higher the oil repellency. The judging criteria are determined by the judgment photo attached to the AATCC 118 method. The grade was determined by the average of n=3 evaluations.
[0120] (Water absorption) The water absorption was evaluated according to the water absorption rate method (drop method) of JISL1907 (2010 edition).
[0121] (elongation recovery rate) Using a constant-speed extension tensile tester with a self-recording device, the specimen was attached with a grip distance of 20 cm under an initial load of 0.0826 cN per dtex, stretched to 20% elongation at a tensile speed of 20 cm / min, and immediately removed at the same speed. After complete removal of the weight, the specimen was immediately stretched to the initial load, and the recovery elongation at this time was recorded as the elongation recovery rate.
[0122] (fabric elongation rate) The fabric elongation rates in the warp and weft directions were measured using JIS L-1096 Elongation Rate Method A (constant speed elongation method).
[0123] (Soil release evaluation) The soil release performance against oily stains was evaluated according to JIS-L1919 "Testing Methods for Stain Resistance of Textile Products" (2006 edition), Method C. A contaminant (oil red content 0.1%) was prepared using the components of lipophilic contaminant-2 specified in JIS-L1919 "Testing Methods for Stain Resistance of Textile Products" (2006 edition), Method C, and the test was carried out according to the following procedure.
[0124] A PET film was placed on the square filter paper, and a piece of fabric cut to 8cm x 8cm was placed on top of it. 0.1mL of oily soil was dropped from a height of 10cm and left for 30 seconds. A circular piece of filter paper was placed on top and the soil was absorbed by the weight of the filter paper. The position of the filter paper was then shifted and the soil was absorbed again by the part of the filter paper that was not soiled. This operation was repeated until the filter paper no longer absorbed the soil. If the filter paper did not touch the contaminated part, both ends of the filter paper were held, and the filter paper was brought into contact with the soil and absorbed with as little weight as possible. The contaminated fabric was then sewn together to a size of about 40cm x about 40cm, and within one hour after the dropping of the contaminant, the washing time was reduced to half of the washing conditions of the ISO6330C4N method and washed. As an exception, Comparative Examples 6, 7, and 8 were washed for the normal washing time.
[0125] If there was not enough soiled fabric, waste fabric was sewn in. The stain resistance grade was judged under a D65 light source using the JIS L0805 (2005 edition) stain color gray scale. There are five grades, from 1 to 5, and the higher the number, the higher the soil release property. From the viewpoints of wearing comfort and reducing fiber waste, a higher soil release property is preferable.
[0126] (Weight measurement of textile waste) The aqueous solution containing the fiber waste was filtered by suction using a polycarbonate membrane (K040A047A, pore size 0.4 μm, manufactured by Advantec Toyo Co., Ltd.) whose mass had been measured in advance. The polycarbonate membrane and fiber waste after filtration were dried at 105°C for 1 hour, and then their masses were measured. The difference between the masses before and after filtration was taken as the amount of fiber waste.
[0127] (Method for measuring the amount of fiber waste generated from a piece of fabric) A piece of fabric was cut to 32 cm length by 32 cm width, and 20 mm wide sealing tape E302 (Toray Coatex Co., Ltd.) was temporarily attached around the edge, within a range of 1.0 cm from the edge of the fabric, with half of the sealing tape protruding. After the four sides were temporarily attached, sealing tape was similarly attached from the other side, and the edge of the fabric was sandwiched between two pieces of sealing tape. The adhesive area between the sealing tape and the edge of the fabric was sewn with sewing thread using a lockstitch sewing machine (polyester filament sewing thread, stitch count: 13 stitches / 3.0 cm) to prevent it from peeling off. Furthermore, it was pressed for 5 seconds at 0.6 MPa and 130°C using an air-driven fully automatic transfer press HP-4536A-12 (Hashima Co., Ltd.) to perform the permanent adhesion, and a test specimen (effective evaluation area: 900 cm) was prepared. 2 ) was prepared.
[0128] Washing is performed according to the ISO 6330 C4N method without putting the laundry, the load cloth, or the detergent in the washing machine, and the washing machine is cleaned. With a collection bag manufactured using a nylon screen NY10-HC (manufactured by Fluoro Industries Co., Ltd.) with a mesh size of 10 μm attached to the drain of the washing machine, two fabric sample pieces prepared were placed in the washing machine, and washing was performed with the washing time reduced to half of the washing conditions of the ISO 6330 C4N method. As an exception, for Comparative Examples 6, 7, and 8, washing was performed for the normal washing time. However, detergent and load cloth were not used. In addition, the filters for collecting lint attached to the washing machine were removed and used, and after washing, the fiber waste attached to the nylon screen was collected with pure water and suction filtered using a polycarbonate membrane filter (K040A047A Advantec Toyo Co., Ltd.) whose mass had been measured in advance. After filtration, the polycarbonate membrane and fiber waste are dried at 105°C for 1 hour, and their masses are measured. The difference between the masses before and after filtration is regarded as the amount of fiber waste generated.
[0129] (Actual wear test) A dress shirt made using the fiber structure described in the Examples and Comparative Examples was worn, and after 7 hours of office work and 1 hour of break time (including a 30-minute meal (one portion of curry rice)), it was washed at home and worn again the next day. This cycle was continued for a total of 10 days, and then evaluation was performed from three perspectives: comfort, ease of removing dirt that had adhered during meals, and unpleasant odor after repeated use. In addition, in the 10-day wear evaluation, the washing time was reduced to half that of the basic washing, but if dirt was a concern, it was allowed to wash for the normal washing time at the wearer's discretion. After washing, the shirt was hung to dry in the shade for 7 hours, and although it was dry, it was not ironed or otherwise worn the next day. Each item was rated on a four-point scale of A, B, C, and D, with A being the most comfortable to wear and D being the least comfortable, A being the most excellent in terms of stain removal and D being the least excellent, and A being the least effective in terms of unpleasant odors after repeated use and A being the absence of unpleasant odors after repeated use and D being the presence of unpleasant odors after repeated use. Details are provided below.
[0130] (Comfort) A: It has excellent stretchability and is very comfortable to wear. B: It has some stretchability, so it is comfortable to wear. C: It had little stretch and was uncomfortable to wear. D: It had little stretch and was very uncomfortable to wear.
[0131] (Easy to remove dirt) A: The stains were removed even when the wash time was cut in half. B: When I washed the clothes for half the time, some dirt remained, but it was almost completely removed. C: When I washed the clothes for half the time, some dirt remained, and even when I washed them for the normal time, some dirt remained. D: When I washed the clothes with half the wash time, the dirt remained, and even with the normal wash time, most of the dirt remained.
[0132] (Unpleasant odor after repeated use) A: It was hard to get an unpleasant odor when worn repeatedly. B: A slight unpleasant odor was observed when wearing repeatedly. C: An unpleasant odor was generated when worn repeatedly. D: An unpleasant odor was observed when the garment was worn repeatedly.
[0133] (Production of polyester resin containing polyether component) A polyester resin was obtained by mixing a polyester component of terephthalic acid and ethylene glycol as a hard segment made of polyester and a polyethylene glycol component as a soft segment made of a polyether component in an arbitrary ratio and simultaneously carrying out a condensation reaction.
[0134] Example 1 The fabric is a plain weave fabric (weight: 175g / m) woven to a weave density of 133 threads / 2.54cm in the warp and 76 threads / 2.54cm in the weft, using 45-count ring-spun yarn with 867T / m twist in the S direction and 65% full-dull PET staple fiber (fiber length 38mm, fineness 0.89dtex) / 35% cotton as the warp yarn, and PET / PBT 30dtex / 24F bimetal type latent crimp composite fiber with Z-direction latent torque spun to a mass ratio of 50:50 with long fiber PET:PBT as the core yarn, and 45-count composite ring-spun yarn with 1024T / m twist in the S direction and 65% full-dull PET staple fiber (fiber length 38mm, fineness 0.89dtex) / 35% cotton as the sheath yarn. 2 The fabric was scoured, bleached, and intermediate set in the usual manner.
[0135] The fabric was immersed in a processing solution containing water as a solvent, 30 g / L of TM-SS21 (manufactured by Matsumoto Yushi Seiyaku Co., Ltd., a block copolymer (copolyester) composed of polyester units composed of terephthalic acid and / or isophthalic acid and alkylene glycol, and polyalkylene glycol units, solid content 10% by mass), 10 g / L of "Nikkanon (registered trademark)" ZP-700 (manufactured by Nicca Chemical Co., Ltd., a pyridine-based antibacterial agent, solid content 19%), and 0.5 g / L of acetic acid, and was squeezed so that the pick-up rate was 90% by mass. The solution was then heat-treated at 130°C for 2 minutes and then at 170°C for 1 minute to obtain a fiber structure of the present invention. The measurement and evaluation results of the fiber structure obtained in Example 1 are shown in Table 1. As the polyether component, the presence of a polyethylene glycol component was confirmed. Moreover, the fiber structure obtained in Example 1 had a water repellency of grade 1, an oil repellency of grade 0, and a water absorbency of 1 second.
[0136] Example 2 The same fabric as in Example 1 was used.
[0137] The above fabric was immersed in a processing solution containing 90 g / L of "Palazine" KFS-100 (manufactured by Keihin Chemical Industry Co., Ltd., weak water- and oil-repellent fluorine-based oil-repellent resin, solid content 10%, polyoxyethylene group-containing, water repellency grade 2, oil repellency grade 6, water absorption 60 seconds or more) (polyoxyalkylene group-containing fluorine-based water- and oil-repellent resin), 18 g / L of polyvinyl alcohol (solid content 10%, average polymerization degree 500, saponification degree 90%), 4.5 g / L of "Amidea (registered trademark)" M-3 (triazine ring-containing compound manufactured by DIC Corporation: solid content 80%), and 0.75 g / L of "Catalyst" ACX (catalyst manufactured by DIC Corporation, catalyst, solid content 3%), and then squeezed to a pickup rate of 90 mass%, followed by heat treatment at 130 ° C for 2 minutes and then heat treatment at 170 ° C for 1 minute to obtain a fiber structure of the present invention. The measurement and evaluation results of the fiber structure obtained in Example 2 are shown in Table 1. Furthermore, the fiber structure obtained in Example 2 had a water repellency of grade 2, an oil repellency of grade 6, and a water absorbency of 60 seconds or more.
[0138] Example 3 The same fabric as in Example 1 was used.
[0139] The above fabric was immersed in a processing solution containing water as a solvent, 30 g / L of "Unidyne" TG-5546 (manufactured by Daikin Industries, Ltd.), a fluorine-based water repellent having a perfluoroalkyl group with a carbon number of 6 or less, 3.0 g / L of "Amidea (registered trademark)" M-3 (manufactured by DIC Corporation), 1.0 g / L of "Catalyst" ACX (manufactured by DIC Corporation) as a catalyst for the crosslinking agent, and 10 g / L of 2-isopropanol (manufactured by Nacalai Tesque, Inc.), and squeezed so that the pickup rate is 90 mass%, and then heat-treated at 130 ° C for 2 minutes and then heat-treated at 170 ° C for 1 minute to obtain a fiber structure of the present invention. The measurement and evaluation results of the fiber structure obtained in Example 3 are shown in Table 1. Moreover, the fiber structure obtained in Example 3 had a water repellency of grade 4, an oil repellency of grade 7, and a water absorbency of 60 seconds or more.
[0140] Example 4 The fabric used was a plain weave fabric (weight: 150g / m2) woven to a weave density of 133 / 2.54cm in the warp and 76 / 2.54cm in the weft, with a warp thread of 45-count spun yarn with full dull PET 65% / 35% cotton and a twist of 867T / 2.54cm, a weft thread of PET / PBT 30dtex / 24F eccentric core-sheath type latent crimp composite fiber with a Z-direction torque spun to a mass ratio of 50:50 with PET:PBT as the long fiber, and a short fiber bundle of full dull PET 65% / 35% cotton and a twist of 1024T / 2.54cm in the S direction. This fabric was scoured, bleached, and set in the middle in the usual way.
[0141] The fabric was immersed in a processing solution containing water as a solvent, 30 g / L of TM-SS21 (manufactured by Matsumoto Yushi Seiyaku Co., Ltd., a block copolymer consisting of polyester units made of terephthalic acid and / or isophthalic acid and alkylene glycol, and polyalkylene glycol units, solid content 10%), 10 g / L of "Nikkanon (registered trademark)" ZP-700 (manufactured by Nicca Chemical Co., Ltd., a pyridine-based antibacterial agent, solid content 19%), and 0.5 g / L of acetic acid, and was squeezed so that the pick-up rate was 90 mass%, and then heat-treated at 130°C for 2 minutes and then at 170°C for 1 minute to obtain a fiber structure of the present invention. The measurement and evaluation results of the fiber structure obtained in Example 4 are shown in Table 1. As the polyether component, the presence of a polyethylene glycol component was confirmed. Moreover, the fiber structure obtained in Example 4 had a water repellency of grade 1, an oil repellency of grade 0, and a water absorbency of 1 second.
[0142] Example 5 The same fabric as in Example 1 was used.
[0143] The above fabric was immersed in a processing solution containing 2 g / L of polyester resin P-1, which was produced using polyethylene glycol with a weight average molecular weight of 1700 g / mol and a mass ratio of polyester component to polyethylene glycol component of 1:3 based on the manufacturing method of polyester resin containing the above polyether component, using water as a solvent, and squeezed so that the pick-up rate was 90 mass%, and then heat-treated at 130°C for 2 minutes and then at 170°C for 1 minute to obtain a fiber structure of the present invention. The measurement and evaluation results of the fiber structure obtained in Example 5 are shown in Table 1. As the polyether component, the presence of a polyethylene glycol component was confirmed. Moreover, the fiber structure obtained in Example 5 had a water repellency of grade 1, an oil repellency of grade 0, and a water absorbency of 2 seconds.
[0144] Example 6 The same fabric as in Example 1 was used.
[0145] The above fabric was immersed in a processing solution containing 2 g / L of polyester resin P-2, which was produced using polyethylene glycol with a mass average molecular weight of 5800 g / mol and a mass ratio of polyester component to polyethylene glycol component of 1:3 based on the manufacturing method of the polyester resin containing the above polyether component, using water as a solvent, and squeezed so that the pickup rate was 90 mass%, and then heat-treated at 130°C for 2 minutes and then at 170°C for 1 minute to obtain a fiber structure of the present invention. The measurement and evaluation results of the fiber structure obtained in Example 6 are shown in Table 2. As the polyether component, the presence of a polyethylene glycol component was confirmed. The fiber structure obtained in Example 6 had a water repellency of grade 1, an oil repellency of grade 0, and a water absorbency of 2 seconds.
[0146] Example 7 The same fabric as in Example 1 was used.
[0147] The above fabric was immersed in a processing solution containing 90 g / L of "Palazine" KFS-100 (manufactured by Keihin Chemical Industry Co., Ltd., weak water- and oil-repellent type fluorine-based oil-repellent resin, solid content 10%, polyoxyethylene group-containing, water repellency grade 2, oil repellency grade 6, water absorption 60 seconds or more), 18 g / L, 4.5 g / L of "Amidea (registered trademark)" M-3 (manufactured by DIC Corporation, triazine ring-containing compound: solid content 80%), and 0.75 g / L of "Catalyst" ACX (catalyst manufactured by DIC Corporation, solid content 3%), and then squeezed so that the pickup rate is 90 mass%, followed by heat treatment at 130 ° C for 2 minutes and then heat treatment at 170 ° C for 1 minute to obtain a fiber structure of the present invention. The measurement and evaluation results of the fiber structure obtained in Example 7 are shown in Table 2. The fiber structure obtained in Example 6 had a water repellency grade 2, an oil repellency grade 6, and a water absorption of 60 seconds.
[0148] Example 8 The fabric is a plain weave fabric (weight: 175g / m) woven to a weave density of 133 threads / 2.54cm in the warp and 76 threads / 2.54cm in the weft, using 100% full-dull PET staple fiber (fiber length 38mm, fineness 0.89dtex) 45-count spun yarn with a twist of 867T / m for the warp yarn, 30dtex / 24F bimetal type latent crimp composite fiber with a latent torque in the Z direction spun to a mass ratio of 50:50 PET:PBT for the weft yarn, and 100% full-dull PET staple fiber (fiber length 38mm, fineness 0.89dtex) 45-count composite spun yarn with a twist of 1024T / m in the S direction for the short fiber bundle. 2 The fabric was scoured, bleached, and intermediate set in the usual manner.
[0149] The fabric was immersed in a processing solution containing water as a solvent, 30 g / L of TM-SS21 (manufactured by Matsumoto Yushi Seiyaku Co., Ltd., a block copolymer consisting of polyester units and polyalkylene glycol units formed from terephthalic acid and / or isophthalic acid and alkylene glycol, solid content 10%), 10 g / L of "Nikkanon (registered trademark)" ZP-700 (manufactured by Nicca Chemical Co., Ltd., a pyridine-based antibacterial agent, solid content 19%), and 0.5 g / L of acetic acid, and was squeezed so that the pick-up rate was 90 mass%, and then heat-treated at 130°C for 2 minutes and then at 170°C for 1 minute to obtain a fiber structure of the present invention. The measurement and evaluation results of the fiber structure obtained in Example 8 are shown in Table 2. As the polyether component, the presence of a polyethylene glycol component was confirmed. Moreover, the fiber structure obtained in Example 8 had a water repellency of grade 1, an oil repellency of grade 0, and a water absorbency of 1 second.
[0150] Example 9 The fabric is a plain weave fabric (weight: 175 g / m) woven to a weave density of 133 threads / 2.54 cm, 76 threads / 2.54 cm, using 45-count spun yarn with 35% full-dull PET staple fiber (fiber length 38 mm, fineness 0.89 dtex) / 65% cotton as the warp yarn and 867 T / m twist in the S direction. The weft yarn is a PET / PBT 30 dtex / 24F bimetal type latent crimpable composite fiber with Z-direction torque spun to a mass ratio of 50:50 with long fiber PET:PBT as the core yarn. The short fiber bundle is a 45-count composite spun yarn with 1024 T / m twist in the S direction and 35% full-dull PET staple fiber (fiber length 38 mm, fineness 0.89 dtex) / 65% cotton as the short fiber bundle. 2 The fabric was scoured, bleached, and intermediate set in the usual manner.
[0151] The above fabric was immersed in a processing solution containing water as a solvent, 5 g / L of "Amidea (registered trademark)" M-3 (manufactured by DIC Corporation, 80% by mass aqueous solution of melamine resin monomer), 1 g / L of "Catalyst ACX" (manufactured by DIC Corporation, melamine resin reaction catalyst), 30 g / L of TM-SS21 (manufactured by Matsumoto Yushi Seiyaku Co., Ltd., a block copolymer consisting of polyester units and polyalkylene glycol units consisting of terephthalic acid and / or isophthalic acid and alkylene glycol, solid content 10% by mass), 10 g / L of "Nikkanon (registered trademark)" ZP-700 (manufactured by Nicca Chemical Co., Ltd., pyridine-based antibacterial agent, solid content 19% by mass), and 0.5 g / L of acetic acid, and then squeezed so that the pick-up rate was 90% by mass. The processing solution was then heat-treated at 130°C for 2 minutes and then heat-treated at 170°C for 1 minute to obtain a fiber structure according to the present invention. The measurement and evaluation results of the fiber structure obtained in Example 9 are shown in Table 2. As the polyether component, the presence of a polyethylene glycol component was confirmed. Moreover, the fiber structure obtained in Example 9 had a water repellency of grade 1, an oil repellency of grade 0, and a water absorbency of 1 second.
[0152] Example 10 A circular knit fabric was used using PET / PBT 30dtex / 24F eccentric core-sheath type latent crimpable composite fiber with Z-direction torque spun to a mass ratio of 50:50 for the long fiber PET:PBT as the core yarn, and full-dull PET staple fiber (fiber length 38mm, fineness 0.89dtex) 65% by mass / cotton 35% by mass as the short fiber bundle, with a twist number of 1024T / 2.54cm in the S direction, 45 count composite spun yarn. This fabric was scoured, bleached, and intermediate set in the usual manner.
[0153] The fabric was then immersed in a processing solution containing 30 g / L of TM-SS21 (manufactured by Matsumoto Yushi Seiyaku Co., Ltd., a block copolymer consisting of polyester units made of terephthalic acid and / or isophthalic acid and alkylene glycol, and polyalkylene glycol units, solid content 10% by mass), 0.5 g / L of acetic acid, and Amidea (registered trademark) M-3 (manufactured by DIC Corporation), using water as the solvent, and squeezed so that the pick-up rate was 90% by mass. The solution was then heat-treated at 130°C for 2 minutes and then at 170°C for 1 minute to obtain a fiber structure of the present invention. The measurement and evaluation results of the fiber structure obtained in Example 10 are shown in Table 2. As the polyether component, the presence of a polyethylene glycol component was confirmed. Moreover, the fiber structure obtained in Example 10 had a water repellency of grade 1, an oil repellency of grade 0, and a water absorbency of 1 second.
[0154] Comparative Example 1 The fabric is a plain weave fabric (weight: 175 g / m2) woven to a weave density of 133 threads / 2.54 cm in the warp and 76 threads / 2.54 cm in the weft, using 45-count composite spun yarn with 65% by mass of full-dull PET staple fiber (fiber length 38 mm, fineness 0.89 dtex) / 35% by mass of cotton for the warp and 867T / 2.54cm twist in the S direction. The weft is a core yarn of polyurethane fiber (spandex T-127, 30 dtex) (PU), and 35% by mass of full-dull PET staple fiber (fiber length 38 mm, fineness 0.89 dtex) / 65% by mass of cotton for the short fiber bundle, with 1024T / 2.54cm twist in the S direction. 2 The fabric was scoured, bleached, and intermediate set in the usual manner.
[0155] The fabric was immersed in a processing solution containing water as a solvent, 30 g / L of TM-SS21 (manufactured by Matsumoto Yushi Seiyaku Co., Ltd., a block copolymer consisting of polyester units and polyalkylene glycol units formed from terephthalic acid and / or isophthalic acid and alkylene glycol, solid content 10% by mass), 10 g / L of "Nikkanon (registered trademark)" ZP-700 (manufactured by Nicca Chemical Co., Ltd., a pyridine-based antibacterial agent, solid content 19% by mass), and 0.5 g / L of acetic acid, and was squeezed so that the pick-up rate was 90% by mass. The solution was then heat-treated at 130°C for 2 minutes and then at 170°C for 1 minute to obtain a fiber structure. The measurement and evaluation results of the fiber structure obtained in Comparative Example 1 are shown in Table 3. As the polyether component, the presence of a polyethylene glycol component was confirmed. Moreover, the fiber structure obtained in Comparative Example 1 had a water repellency of grade 1, an oil repellency of grade 0, and a water absorbency of 1 second.
[0156] Comparative Example 2 A fiber structure was obtained without any particular processing using the same fabric as in Example 1. The measurement results of the fiber structure obtained in Comparative Example 2 are shown in Table 3. The fiber structure obtained in Comparative Example 2 had a water repellency of grade 1, an oil repellency of grade 0, and a water absorbency of 5 seconds.
[0157] Comparative Example 3 The same fabric as in Example 1 was used.
[0158] The above fabric was immersed in a processing solution containing 50 g / L of "Neoseed (registered trademark)" NR-158 (Nicca Chemical Co., Ltd., non-fluorinated water-repellent resin, solid content: undisclosed), 4.5 g / L of "Amidea (registered trademark)" M-3 (DIC Corporation, triazine ring-containing compound: solid content 80% by mass), and 0.75 g / L of "Catalyst" ACX (DIC Corporation, catalyst, solid content 3% by mass), and then squeezed so that the pick-up rate was 90% by mass. The fabric was then heat-treated at 130°C for 2 minutes and then at 170°C for 1 minute to obtain a fiber structure of the present invention. The measurement and evaluation results of the fiber structure obtained in Comparative Example 3 are shown in Table 3. Moreover, the fiber structure obtained in Comparative Example 3 had a water repellency of grade 4, an oil repellency of grade 0, and a water absorbency of 60 seconds or more.
[0159] Comparative Example 4 The fabric is a plain weave fabric (weight: 175g / m) woven with 45-count spun yarn with a twist count of 867T / m in the S direction and a warp and weft density of 139 threads / 2.54cm in the warp and 76 threads / 2.54cm in the weft. 2 ) was used. This fabric was scoured, bleached, and intermediate set in a conventional manner, and no particular processing was carried out to obtain a fiber structure of the present invention. The measurement and evaluation results of the fiber structure obtained in Comparative Example 4 are shown in Table 3. Moreover, the fiber structure obtained in Comparative Example 4 had a water repellency of grade 1, an oil repellency of grade 0, and a water absorbency of 20 seconds.
[0160] Comparative Example 5 The same fabric as in Comparative Example 4 was used.
[0161] The fabric was immersed in a processing solution containing water as a solvent, 30 g / L of TM-SS21 (manufactured by Matsumoto Yushi Seiyaku Co., Ltd., a block copolymer consisting of polyester units and polyalkylene glycol units, which are made of terephthalic acid and / or isophthalic acid and alkylene glycol, solid content 10% by mass), 10 g / L of "Nikkanon (registered trademark)" ZP-700 (manufactured by Nicca Chemical Co., Ltd., a pyridine-based antibacterial agent, solid content 19% by mass), and 0.5 g / L of acetic acid, and was squeezed so that the pick-up rate was 90% by mass. The solution was then heat-treated at 130°C for 2 minutes and then at 170°C for 1 minute to obtain a fiber structure. The measurement and evaluation results of the fiber structure obtained in Comparative Example 5 are shown in Table 3. As the polyether component, the presence of a polyethylene glycol component was confirmed. The fiber structure obtained in Comparative Example 5 had a water repellency of grade 1, an oil repellency of grade 0, and a water absorbency of 1 second.
[0162] Comparative Example 6 A fiber structure was obtained without any particular processing using the same fabric as in Comparative Example 1. The fiber structure obtained in Comparative Example 6 was evaluated by changing the washing time. The measurement and evaluation results are shown in Table 4. The fiber structure obtained in Comparative Example 6 had a water repellency of grade 1, an oil repellency of grade 0, and a water absorbency of 10 seconds.
[0163] Comparative Example 7 A fiber structure was obtained using the same fabric and the same processing as in Comparative Example 1. The fiber structure obtained in Comparative Example 7 was evaluated by changing the washing time, and the measurement and evaluation results are shown in Table 4. Moreover, the fiber structure obtained in Comparative Example 7 had a water repellency of grade 1, an oil repellency of grade 0, and a water absorbency of 1 second.
[0164] Comparative Example 8 A fiber structure was obtained without any particular processing using the same fabric as in Comparative Example 4. The fiber structure obtained in Comparative Example 8 was evaluated by changing the washing time. The measurement and evaluation results are shown in Table 4. The fiber structure obtained in Comparative Example 8 had a water repellency of grade 1, an oil repellency of grade 0, and a water absorbency of 20 seconds.
[0165] [Table 1]
[0166] [Table 2]
[0167] [Table 3]
[0168] [Table 4] [Explanation of symbols]
[0169] 1. Component A 2.B component 3. Component A 4.B component 5. Center of gravity a 6. Center of gravity C 7. Minimum thickness S 8. Fiber diameter D 9. Radius of curvature IFR
Claims
1. A fiber structure at least partially using a composite spun yarn composed of long fibers and short fiber bundles, the latent torque direction of the long fiber and the twist direction of the conjugate spun yarn are opposite to each other, and the long fiber is a bimetal type latent crimping conjugate fiber or an eccentric core-sheath type latent crimping conjugate fiber, On the fiber surface Hydrophilic components and / or Fluorine-based water repellent having a perfluoroalkyl group having 6 or less carbon atoms is supported, A textile structure having a soil release property of grade 3 or higher after a stain resistance evaluation.
2. The polyether component is supported on the fiber surface, the weight average molecular weight of the polyether component calculated as polyethylene glycol, as determined by size exclusion chromatography, is in the range of 1,500 to 4,000 g / mol; 2. The fiber structure according to claim 1, wherein the ratio of the weight average molecular weight converted into polyethylene glycol to the number average molecular weight converted into polyethylene glycol is in the range of 1.00 to 1.
35.
3. 3. The fiber structure according to claim 1, wherein at least a part of the fiber surface has a resin coating containing a fluorine-based water- and oil-repellent resin having a polyoxyalkylene group as a hydrophilic component and polyvinyl alcohol.
4. A textile product comprising, at least in part, the textile structure according to any one of claims 1 to 3.
Citation Information
Patent Citations
JP1970007030Y1
JP1975094293A
Production of knitted fabric
JP1997241949A
Long-short composite spun yarn having latent elastic characteristic
JP2000220049A
Covered yarn and knitted or woven fabric thereof
JP2004003042A